2015
DOI: 10.1111/prd.12058
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing in immediately loaded implants

Abstract: The orthopedic field has accumulated ample evidence that bone formation is related to functional loading and in general to physical activity. However, despite evidence that immediately loaded implants can be predictably successful, many clinicians still use the classical (delayed loading) treatment protocol. This paper examines the effects of loading on dental implants and discusses the advantages of immediate loading. The role of loading on augmented alveolar ridges is also addressed and provides evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 70 publications
(79 reference statements)
2
26
0
Order By: Relevance
“…Thus, the unfavorable secondary stability of the IML group could be partially attributed to the inability of atrophic bone to respond rapidly to mechanical loads. These results may also justify the biological responses in the IML group, as bone atrophy is associated with immobilization of the long‐term receptor bone bed, which may in turn affect the vascular support of the bone . These characteristics could delay the formation of a connective tissue rich in vascular units and fibroblasts in direct contact with the surface of the implant, which normally forms during the second week of bone healing .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, the unfavorable secondary stability of the IML group could be partially attributed to the inability of atrophic bone to respond rapidly to mechanical loads. These results may also justify the biological responses in the IML group, as bone atrophy is associated with immobilization of the long‐term receptor bone bed, which may in turn affect the vascular support of the bone . These characteristics could delay the formation of a connective tissue rich in vascular units and fibroblasts in direct contact with the surface of the implant, which normally forms during the second week of bone healing .…”
Section: Discussionmentioning
confidence: 96%
“…However, studies have also shown that mechanical stimuli motivate pre‐osteoblasts to develop bone matrix proteins (osteocalcin) . This eventually results in a significantly higher bone density between the threads of the implant in the IML group (11.6% higher than the CL group) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet our finding of no difference in survival/success rates is in contrast to a previous study of 307 implants supporting two-to four-unit fixed partial dentures in 117 patients. 18 Even so, histological studies suggested clinically stable implants also in heavy smokers after immediate functional loading of implants. Seven implants, most of them in two-unit restorations, accounted for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…9 Immediate loading yielded a 12-month success rate of 97.5% based on 40 implants supporting splinted restorations in 20 patients with missing mandibular premolars and molars. 17 Nonfunctional protocols of immediate loading have been introduced so as to protect newly inserted implants from exposure to any excessive functional or parafunctional forces in partially edentulous patients, 18 as complications like bruxism and severe clenching have been suspected to increase the risk of failure among immediately loaded implants. 17 Nonfunctional protocols of immediate loading have been introduced so as to protect newly inserted implants from exposure to any excessive functional or parafunctional forces in partially edentulous patients, 18 as complications like bruxism and severe clenching have been suspected to increase the risk of failure among immediately loaded implants.…”
mentioning
confidence: 99%